Stress distribution in an infinite elastic body with a covered periodically curved fiber - Kosker, R.; Dikbas, D. M. (SPRINGER, 2009)
Within the frame work of a piecewise homogeneous body model, with the use of the three-dimensional geometrically nonlinear exact equations of elasticity theory, a method is developed for determining the stress distribution in unidirectional fibrous composites with periodically curved fibers. The distribution of the normal and shear stresses acting on interfaces for the case where there exists a bond covering cylinder of constant thickness between the fiber and matrix is considered. The concentration of fibers in the composite is assumed to be low, and the interaction between them is neglected. Numerous numerical results related to the stress distribution in the body considered are obtained, and the influence of geometrical nonlinearity on this distribution is analyzed.
Keywords: fibrous composite; covering material; geometrical nonlinearity; normal stresses; 2 NEIGHBORING FIBERS; STABILITY LOSS; 3-DIMENSIONAL THEORY; COMPOSITE; MECHANICS; ROW; Materials Science; Polymer Science